Physics of Negative Refraction and Negative Index Materials Optical and Electronic Aspects and Diversified Approaches - Krowne, Clifford M.; Zhang, Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book deals with the subject of optical and electronic negative refraction (NR) and negative index materials NIM). Diverse approaches for achieving NR and NIM are covered, such as using photonic crystals, phononic crystals, split-ring resonators (SRRs) and continuous media, focusing of waves, guided-wave behavior, and nonlinear effects. Specific topics treated are polariton theory for LHMs (left handed materials), focusing of waves, guided-wave behavior, nonlinear optical effects, magnetic LHM composites, SRR-rod realizations, low-loss guided-wave bands using SRR-rods unit cells as LHMs, NR of electromagnetic and electronic waves in uniform media, field distributions in LHM guided-wave structures, dielectric and ferroelectric NR bicrystal heterostructures, LH metamaterial photonic-crystal lenses, subwavelength focusing of LHM/NR photonic crystals, focusing of sound with NR and NIMs, and LHM quasi-crystal materials for focusing.
Negative Refraction of Electromagnetic and Electronic Waves in Uniform Media -- Anisotropic Field Distributions in Left-Handed Guided Wave Electronic Structures and Negative Refractive Bicrystal Heterostructures -- (3z(BLeft-Handed(3y (BMagnetic Granular Composites -- Spatial Dispersion, Polaritons, and Negative Refraction -- Negative Refraction in Photonic Crystals -- Negative Refraction and Subwavelength Focusing in Two-Dimensional Photonic Crystals -- Negative Refraction and Imaging with Quasicrystals -- Generalizing the Concept of Negative Medium to Acoustic Waves -- Experiments and Simulations of Microwave Negative Refraction in Split Ring and Wire Array Negative Index Materials, 2D Split-Ring Resonator and 2D Metallic Disk Photonic Crystals -- Super Low Loss Guided Wave Bands Using Split Ring Resonator-Rod Assemblies as Left-Handed Materials -- Development of Negative Index of Refraction Metamaterials with Split Ring Resonators and Wires for RF Lens Applications -- Nonlinear Effects in Left-Handed Metamaterials.s
Keywords: Physics; Condensed matter; Optics; Optoelectronics; Plasmons (Physics).; Engineering; Optical materials; Electronic materials; Physics; Condensed Matter Physics; Optical and Electronic Materials; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Electronic books